Pengaruh Kontrak Bagi Hasil, Kualitas Komunikasi dan Kepercayaan terhadap Kolaborasi Rantai Pasok. - Rahmat Hidayat, yayat; Sabila, Ilfani Nuralfiyan (lembaga penelitian universitas swadaya gunung jati, 2026)
This research aims to analyze the effect of revenue sharing contracts on supply chain collaboration. This research uses the Multiple Linear Regression Method, namely a regression model that involves more than one independent variable and to find out how much influence the independent variable has on the dependent variable. The research location is the dairy cattle cooperative in Cipari sub-district, Cigugur sub-district. The research respondents were 74 people from 282 populations with a sampling technique using the Slovin formula. The research results show that there is a significant influence on revenue sharing contracts on supply chain collaboration